Recent Advances in Chitosan-Based Metal Nanocomposites for Wound Healing Applications - Kai Wang; Su Pan; Zhiping Qi; Peng Xia; Haotian Xu; Weijian Kong; Hongru Li; Pan Xue; Xiaoyu Yang; Chuan Fu (Advances in Materials Science and Engineering)
Chitosan (CS) has been extensively studied as a natural polymer, in the field of wound repair, due to its useful properties, which include a lack of toxicity and stimulation, excellent biological affinity, degradability, and promotion of collagen deposition. However, inferior mechanical strength and moderate antibacterial properties are the drawbacks restricting its further clinical application. Many researchers have adopted the use of nanotechnology, in particular metallic nanoparticles (MNPs), in order to improve the mechanical strength and specific antibacterial properties of chitosan composites, with promising results. Furthermore, chitosan naturally functions as a reducing agent for MNPs, which can also reduce cytotoxicity. Thus, CS, in combination with MNPs, exhibits antibacterial activity, excellent mechanical strength, and anti-inflammatory properties, and it has great potential to accelerate the process of wound healing. This review discusses the current use of CS and MNPs in wound healing and emphasises the synergy and the advantages for various applications in wound healing.